2015
DOI: 10.1542/peds.2015-0676
|View full text |Cite
|
Sign up to set email alerts
|

Laser Acupuncture for Neonatal Abstinence Syndrome: A Randomized Controlled Trial

Abstract: BACKGROUND: Neonatal abstinence syndrome (NAS) is usually treated with opiate derivatives and supported with nonpharmacological treatment.METHODS: This prospective, randomized, controlled, blinded, single-center study was carried out between March 2009 and November 2014. Newborn infants diagnosed with NAS after maternal opioid substitution therapy were eligible for inclusion. Infants were randomly allocated to the acupuncture group (combining laser acupuncture and pharmacological therapy of morphine and phenob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 51 publications
1
67
0
Order By: Relevance
“…The included studies all originated in high‐resource countries including the United States (n = 9), Canada (n = 3), Austria (n = 1), and the United Kingdom (n = 1) . The quality improvement and cohort studies were appraised as fair to good methodologically, with all meeting a minimum of eight of the 16 quality content domains (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies all originated in high‐resource countries including the United States (n = 9), Canada (n = 3), Austria (n = 1), and the United Kingdom (n = 1) . The quality improvement and cohort studies were appraised as fair to good methodologically, with all meeting a minimum of eight of the 16 quality content domains (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The quality improvement and cohort studies were appraised as fair to good methodologically, with all meeting a minimum of eight of the 16 quality content domains (Table ). The remaining five studies included a randomized controlled trial, case series, a cohort study, and a phenomenological study . A common study limitation of these was the variability of the study populations (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been used to treat neonatal abstinence syndrome [8]. NESAP, a non-invasive method of stimulation of acupuncture points, has been shown to be safe in neonates [9].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence for use in myofacial pain [4,36] and numerous other conditions [4]. In children, LA reduces intensity and number of migraine headaches [23], decreases vomiting in post-operative settings [51], and reduces duration of morphine therapy and hospital stay in neonatal abstinence syndrome infants [44]. Several studies have shown laser acupuncture is as effective as traditional acupuncture using needles.…”
Section: Introductionmentioning
confidence: 99%